2022
DOI: 10.1007/s12144-022-02829-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between dispositional mindfulness and empathy among undergraduate nursing students: A multicenter cross-sectional study

Abstract: The aim of this study was to explore the role of gender, age, and academic year in shaping dispositional mindfulness (DM) and the association between DM facets and empathy dimensions in a sample of undergraduate nursing students. In a multicenter cross-sectional study design, the Five Facet Mindfulness Questionnaire (FFMQ), the Interpersonal Reactivity Index (IRI), and socio-demographic questions were administrated to a convenience sample of Italian nursing students. 622 nursing students (82.2% female) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In fact, some previous studies reported a positive correlation between meditative mindfulness and socio-cognitive mindfulness [13,28,68]. Positive correlations between meditative mindfulness and empathy have also been found in previous studies [69,70], including those in the nursing field [14,18,21,25,26].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In fact, some previous studies reported a positive correlation between meditative mindfulness and socio-cognitive mindfulness [13,28,68]. Positive correlations between meditative mindfulness and empathy have also been found in previous studies [69,70], including those in the nursing field [14,18,21,25,26].…”
Section: Discussionmentioning
confidence: 62%
“…For nursing students, mindfulness intervention was effective in alleviating stress [21][22][23], depression [22,23], and anxiety [21][22][23]. In addition, a higher level of mindfulness was linked to enhancing nursing students' sense of well-being [21], a reappraisal emotion strategy [24], empathy [21,25,26], self-esteem [27], and academic outcomes [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, dispositional mindfulness would predict CSE, which in turn would predict increased levels of well-being. Furthermore, past research studies have found significant differences in mindfulness with respect to gender (Ardenghi et al, 2022). Males have been found to score higher on dispositional mindfulness than females (Alispahic & Hasanbegovic-Anic, 2017).…”
Section: The Mediating Role Of Core Self-evaluationmentioning
confidence: 98%
“…Meanwhile, the literature has found that mindfulness was positively correlated with empathy among university students [ 23 , 24 , 25 ]. Considerable studies have also supported that mindfulness-based interventions improved university students’ empathy [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%